BS ISO 12167-1. Plain bearings. Hydrostatic plain journal bearings with drainage grooves under steady-state conditions. Part 1. Calculation of oil-lubricated plain journal bearings with drainage grooves (22nd September 2022) - British Standards Institution,
No abstract available